A possibilidade de registro civil da dupla paternidade em casos de adoção homoafetiva: uma análise a partir do princípio do melhor interesse da criança - Barcelos, Maiki Anjolin (Universidade do Vale do Rio dos Sinos, 2018)
This paper discusses about the possibility of civil registration of dual paternity in cases of homoaffective adoption. First of all, will be presented the family’s evolution in the Brazilian legal system, in order to demonstrate that the concept transcends the idea of union between man and woman. Here, will give attention to the pluralism existing in Family relationships, the new modalities of families and also the challenges presented to the law in face of the new family configurations. Likewise, the recognition of multiparentality and its concept will be analyzed, demonstrating the possibility of both biological and socio-affective paternity, provided that the best interest of the infant is safeguarded. Regarding multiparentality, attention will also be given to legal reflexions based on existing jurisprudential understanding. In addition, the legal possibility of homoaffective adoption will be brought to light in the light of the best interests of the child, focusing on the adoption modalities, the legal requirements for its perfectibilization and the consequences of that act. The method of approach of this work is deductive. The procedure adopted was monographic. The research technique used was the bibliographical and jurisprudential research. The main focus of the research is centered on the demonstration of the legal feasibility of multiparentality, specifically regarding the possibility of civil registration of double paternity in cases of adoption by homoaffective couples.
Keywords: Família; Multiparentalidade; Adoção homoafetiva; Princípio do melhor interesse da criança; Family; Multiparentality; Homoaffective adoption; Civil registry; Principle of the child’s best interest; Registro civil